Intuitive Spatial Drawing System based on Hand Interface - Ginam Ko(고기남); Serim Kim(김세림); YoungEun Kim(김영은); SangHun Nam(남상훈) (디지털콘텐츠학회논문지, 2017)
The development of Virtual Reality (VR)-related technologies has resulted in the improved performance of VR devices as well as affordable price arrangements, granting many users easy access to VR technology. VR drawing applications are not complicated for users and are also highly mature, being used for education, performances, and more. For controller-based spatial drawing interfaces, the user's drawing interface becomes constrained by the controller. This study proposes hand interaction based spatial drawing system where the user, who has never used the controller before, can intuitively use the drawing application by mounting LEAP Motion at the front of the Head Mounted Display (HMD). This traces the motion of the user’s hand in front of the HMD to draw curved surfaces in virtual environments. KCI Citation Count: 0